Menstrual hygiene practices among adolescent girls in a resettlement colony of Delhi: a cross-sectional study - Sharma, Shantanu; Mehra, Devika; Kohli, Charu; Singh, M. M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Menarche is an important milestone in the life of a girl which signifies the onset of fertility in a woman. To understand the health consequences and importance of menstrual hygiene practices among adolescent girls, it is important to study the current practices about the same so that future interventions can be planned accordingly. Methods: This study adopted a cross-sectional study design. A total of 85 adolescent girls (10-19 years old) were interviewed by the investigator over a period of 3 months (Jan-Mar 2015). Data were analyzed using the software SPSS version 17. Results: Out of 85 adolescent girls studied, the majority was between 15 to 19 years. In our study 71(83.5%) out of 85 adolescent girls had already started their menstruation. The mean (±SD) age of menarche in the study subjects was 11.4±5.3 years. Around 33 out of 71 (46.4%) girls practiced different restrictions during menstruation. Out of 71 (85.9%) girls used sanitary pads during menstruation. In cases of reused cloth, the place of its drying was observed, responses stated were; outside the house in sunlight in 1 (5.8%) girl, 14 (82.2%) dried them inside the house, and 2 (11.7%) girls dried them outside in a dark place. Conclusions: It is imperative to strengthen the menstrual hygiene management (MHM) programs of the country and have a greater outreach. Multiple strategies need to be used to address this such as education on reproductive health and menstruation provided in schools, media campaign’s and improving water and sanitation for improving school retention of adolescent girls and their overall health.